Introducing the Effective Mass of Activated Complex and the Discussion on the Wave Function of this Instanton - Ptáček, Petr; Opravil, Tomáš; Šoukal, František (IntechOpen, 2018)
Heterogeneous kinetics plays an important role in many scientific disciplines and industrial branches such as physical chemistry, materials science, chemical industry, ceramic industry, etc. Although many excellent books on theories and methods can be found, the aim of this book is to provide an unconventional insight into the heterogeneous kinetics and properties of the activated complex. The introduction of the effective mass of this instanton enables to calculate many other properties, such as the most probable speed of activated complex, the momentum, the energetic density, the mass flux, etc., and to define two quantum numbers of activated state, i.e., the activation energy and the momentum. The monograph is organized into three chapters. The first of them deals with a short historical background, which introduces the beginning of chemical kinetics in the historical context. The second chapter is dedicated to the transition state theory, and the third one explains the concept of effective mass and effective rate of activated state as well as other properties of activated complex.